Socioeconomic and environmental impacts of reforestation in Luz de América, Ecuador - Bautista-Espinoza, Hugo; Moreno-Muñoz, Mario; Argotti-Valencia, Eduardo; Jiménez-Pozo, Patricio (EASI: Engineering and Applied Sciences in Industry, 2024)
This study shows how forest landscape restoration (FLR) initiatives impact ecology, livelihoods and social cohesion from the perspective of rural communities. To obtain data, 5 focus discussion groups were formed in the communities in the Luz de América parish, which since 2015 have worked together with the University of the Armed Forces (ESPE) on reforestation projects. A coding process was conducted to identify key themes and patterns that reveal the impacts of forest landscape restoration. The results indicate that FLR initiatives have promoted social cohesion and conflict resolution. This is evidenced through the establishment of Tsáchilas Community Organizations (TCO), the volunteer participation of agricultural engineering students and ESPE teachers. Among the impacts on the environment, we have: the restoration of biodiversity, improvement of living conditions for rural populations, better soil and water quality. Reforestation has improved the livelihoods of communities. The community members affirm that there is an increase in agricultural productivity, access to education, food security and better economic conditions. The authors encourage Ecuador to support and strengthen forest landscape restoration initiatives all around the country to improve social equity and productivity.
Keywords: Reforestation; ecosystem restoration; sustainability; focus group discussions; social cohesion development; indigenous communities